2018
DOI: 10.1111/apm.12856
|View full text |Cite
|
Sign up to set email alerts
|

LAMP‐1 gene is overexpressed in high grade glioma

Abstract: High-grade gliomas (HGG) are the most frequent brain tumors in adults. Glioblastoma multiforme (GBM) is their most aggressive form resistant to therapy. It was shown that inhibition of autophagy reduced GBM development and autophagy interfering agents are regarded as a new strategy to fight glioma cells. The lysosome-associated membrane proteins (LAMPs) display differential expression particularly in cancer. There are few data on their expression and especially on their molecular profile. The aim of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…While we did not observe significant changes in LAMP1 expression, Jensen et al [59] found that LAMP1 is more highly expressed in glioblastoma than in diffuse and anaplastic astrocytomas, even though its expression does not correlate with the overall survival of the patient [59,60]. CTBP1/BARS and its downstream target PLD1 , whose activation triggers the closure and the final fission of macropinosomes from the plasma membrane [9,61,62], were found downregulated in high-grade tumors at the mRNA level herein.…”
Section: Discussioncontrasting
confidence: 57%
“…While we did not observe significant changes in LAMP1 expression, Jensen et al [59] found that LAMP1 is more highly expressed in glioblastoma than in diffuse and anaplastic astrocytomas, even though its expression does not correlate with the overall survival of the patient [59,60]. CTBP1/BARS and its downstream target PLD1 , whose activation triggers the closure and the final fission of macropinosomes from the plasma membrane [9,61,62], were found downregulated in high-grade tumors at the mRNA level herein.…”
Section: Discussioncontrasting
confidence: 57%
“…Whereas it was published that LAMP-1 is constitutively expressed, the specific LAMP-2 expression is known to vary greatly with the cell type 50 . Moreover, the LAMP-1 gene was recently shown to be overexpressed in malignant gliomas 25 . Machado and colleagues also described that lysosomal exocytosis, which is also mainly mediated by LAMP-1, plays a primary role in tumour progression and chemoresistance 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the expression of both glycoproteins is linked to each other, which results in a LAMP-1/LAMP-2-homeostasis. Interestingly, LAMP-1 and LAMP-2 expression has been observed in various tumours and has been shown to correlate with a high metastatic potential 23 , 24 , whereas LAMP-1 was also published to be overexpressed in some glioblastomas 25 . In context with cancer, autophagy in general also plays a critical role in the survival of cancerogenic cells undergoing starvation due to deficiencies in nutrition supply within the tumour microenvironment 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of LAMP1 has been linked to high-grade breast tumors capable of metastasis; hence, its high expression appears to be associated with malignant attributes [ 30 ]. Recent studies have shown LAMP1 overexpression of both mRNA and protein levels in high-grade glioblastoma multiforme (GBM) [ 31 ]. Moreover, high expression levels of LAMP1 in the plasma membrane were observed, inter alia, in colorectal neoplasm tissues, advanced prostate cancer (PCa), and castration-resistant prostate cancer (CRPC) [ 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%